Addressing formulation issues of syariah compliant generic sustained release antidiabetic solid dosage form. - Mohd Nawi, Mohamed Sufian; Abul Bashar Mohammed, Helaluddin; Kasmuri, Abdul Razak; Tan, Soo Choon (2018)
Gliclazide (1-(3,3a,4,5,6,6a-hexahydro-1H-cyclopenta[c]pyrrol-2-yl)-3-(4-methylphenyl)sulfonylurea) is a second-generation sulfonylurea which is orally administered in the treatment of non-insulin-dependent diabetes mellitus in adults. Sustain release drugs help to improve drugs bioavailability by controlling the time of drug release or prolonging it. We are reporting the formulations of 60 mg sustain release gliclazide tablets with careful choice of all the ingredients and processes related to syariah compliance manufacturing of pharmaceutical products. In this work, different ratios of xanthan gum, a natural gum and hydroxypropyl methylcellulose (HPMC) had been used as the release retardants to achieve the sustain release criteria. The tablets were produced by wet granulation and semi-automatic tableting process. All the formulations were evaluated for the thickness, hardness, friability, weight variation, content of active ingredient, and in vitro dissolution profile following the British Pharmacopoeia (BP) criteria. Tablet assay of active pharmaceutical ingredient (High Performance Liquid Chromatography [HPLC] method) was adopted from British Pharmacopoeia (BP) with some modification. The HPLC method validation covered the specificity, linearity, range, accuracy, precision, limit of detection (LOD), and limit of quantitation (LOQ). We expect that the outcome of our study could be useful for the formulation of such product that will be helpful for the Muslim patient especially during the fasting month.